Risks Management of Ready-Made Garments Industry in Bangladesh - Hasan, Md. Morshadul; Mahmud, Appel (International Research Journal of Business Studies, 2017)
The primary objective of this paper is to identify the associated risks in readymade garments sector and find out the ways how these risks can be mitigated. The sample respondents are selected from the different company in different locations, and different level of the respondents are interviewed for collecting information randomly from 45 garments factory from the total population size 4328 company. It has been found in this research that almost all the risks are properly controlled or managed by the responsible parties. The responsible parties of controlling risks are trying most to control the risks. There is few past research about risks management of ready-made garments industry in Bangladesh. Different types of risks and the risks controlling technique will be discussed in the letter part of this research.